PENERAPAN LITERASI DIGITAL di SMP NEGERI 20 SURAKARTA - Fairly Fabiola Hendrik Fernanda; Laili Etika Rahmawati; Irsha Oktavimadani Putri; Risma Nur’aini (Buletin Literasi Budaya Sekolah, 2020)
The phenomenon of using social media as online media has increasingly developed in this decade. Young people as a millennial or digital native generation are the biggest users in the use of social media today. In implementing digital literacy schools must monitor students in accessing social media. So the teachers must really be able to supervise and sort out digital literacy that is suitable for their students. In learning activities students prefer digital literacy that is applied compared to normal teaching and learning activities. Because in digital literacy learning students more easily understand every material delivered. This study aims to determine the good and bad effects of the application of digital literacy in schools today. The method used in this research is qualitative. So the teachers can apply it properly and correctly. Teachers must be smarter and more creative in developing digital literacy in the learning taught. So that digital literacy can be used and utilized by teachers in conducting learning.